Complete mitochondrial genome of the Blue Eared Pheasant, Crossoptilon auritum (Galliformes: Phasianidae). (2nd January 2016) - Ren, Qiongqiong; Li, Xifeng; Yuan, Jian; Chen, Dongsheng; Zhang, Lei; Guo, Weiwei; Jiang, Lan; Wang, Ping; Kan, Xianzhao
Abstract: The circular mitochondrial genome of Crossoptilon auritum is 16, 687 bp in length, containing 13 protein-coding genes (PCGs), 2 ribosomal RNA genes, 22 transfer RNA ( tRNA ) genes, and a putative control region. All of the genes encoded on the H-strand, except for one PCG (nad6) and eight tRNA genes ( tRNA Gln, tRNA Ala, tRNA Asn, tRNA Cys, tRNA Tyr, tRNA Ser (UCN), tRNA Pro, and tRNA Glu ), as found in many other birds' mitochondrial genomes. All of these PCGs are initiated with ATG, except for cox1 and nad5, which began with GTG, while stopped by four types of stop codons. All tRNA genes have the potential to fold into typical clover-leaf structure. Phylogenetic analysis indicated that the genus Crossoptilon was the sister of the genus Lophura .